Readiness of small and medium enterprises to apply total quality management standards: Evidence from Kosovo - Engelbert Zefaj (Problems and Perspectives in Management)
Applying effective management methods for small and medium enterprises (SMEs) is a crucial commitment to compete in the market. Total quality management (TQM) is a well-known systematic method that increases business competitiveness and improves performance. Accordingly, the purpose of this paper is to examine the gap between current SMEs’ management quality in relation to the management standards recommended by TQM. This quantitative research was conducted with representatives of 76 relevant SMEs out of 370 contacted through the official platform for business registration. Firstly, 12 relevant critical success factors (CSFs) have been identified and validated with Cronbach’s alpha and item statistics and further applied to measure SMEs’ performance. One sample statistic is applied for CSF indexing, and one sample t-test is used to test the raised hypothesis. According to the research findings, human resource management performs with an average score of 3.95 out of 5, information management 3.89 out of 5, and continuous improvement 3.77 out of 5, while customer focus performs with a low score of 3.32 out of 5, and training and education with 3.14 out of 5. The raised hypothesis confirms that SMEs are not at the level of TQM standards, and this is supported by a reliability value of alpha (p = 0). This paper contributes to the literature by providing insights into current SMEs’ management quality and offers a validated model, which can be applied to measure SMEs’ managerial quality.